The endoscopic evaluation of the oesophageal phase of swallowing (E-FEES): perspective in a audiological-phoniatric setting. (3rd July 2019) - Farneti, Daniele; Genovese, Elisabetta
Abstract: During a fiberoptic endoscopic evaluation of swallowing (FEES) the study of the oesophagus, complete with tests with bolus (oesophageal FEES, E-FEES) is a procedure rarely used in a phoniatric setting, with patients complaining of swallowing and voice alterations. This extension of FEES toward the oesophagus by a transnasal approach is a procedure used for decades in the instrumental evaluation of patients with ENT complaints. E-FEES is used on out-patients without premedication or local anaesthesia. The patient is sitting upright and a 70 cm flexible endoscope, 3.5 cm diameter, is used. During the procedure the patients undergo tests with bolus. 20 patients (13M/7F, range 19–78 years, mean age 50, 51 years), taken from 437 consecutive outpatients seen in our Department from August to December 2011, underwent E-FEES (retrospective analysis). Patients were selected based on a reflux finding index (RFI) > 13, Reflux finding score (RFS) > 7 and FEES alterations (penetration/aspiration, spillage, residues). E-FEES findings were: 10 esophagitis, 1 gastroesophageal junction incontinence, 2 hiatal hernia, 4 motility alterations, 2 diverticula, 1 carcinoma. oesophageal alterations are not rare in patients with deglutition and voice disorders. E-FEES is a safe, reliable and cost-effective technique, worthy of being implemented in a phoniatric setting. The main steps and characteristic of the procedure are proposed.